Lactic acidosis secondary to metformin overdose: a case report - Timbrell, Simon; Wilbourn, Gary; Harper, James; Liddle, Alan (Biomed Central, 2012)
Introduction Metformin is a commonly used treatment modality in type 2 diabetes mellitus, with a well documented side effect of lactic acidosis. In the intensive care setting lactate and pH levels are regularly used as a useful predictor of poor prognosis. In this article we highlight how high lactate levels are not an accurate predictor of mortality in deliberate metformin overdose.